Precipitation stable isotopic signatures of tropical cyclones in Metropolitan Manila, Philippines, show significant negative isotopic excursions - Jackisch, Dominik (2022)
Tropical cyclones have devastating impacts on the environment, economies, and societies and may intensify in the coming decades due to climate change. Stable water isotopes serve as tracers of the hydrological cycle, as isotope fractionation processes leave distinct precipitation isotopic signatures. Here we present a record of daily precipitation isotope measurements from March 2014 to October 2015 for Metropolitan Manila, a first-of-a-kind dataset for the Philippines and Southeast Asia. We show that precipitation isotopic variation at our study site is closely related to tropical cyclones. The most negative shift in δ18O values (-13.84ĝ€¯‰) leading to a clear isotopic signal was caused by Typhoon Rammasun, which directly hit Metropolitan Manila. The average δ18O value of precipitation associated with tropical cyclones is -10.24ĝ€¯‰, whereas the mean isotopic value for rainfall associated with non-cyclone events is -5.29ĝ€¯‰. Further, the closer the storm track is to the sampling site, the more negative the isotopic values are, indicating that in situ isotope measurements can provide a direct linkage between isotopes and typhoon activities in the Philippines.